RANCANG BANGUN SISTEM APLIKASI PEMESANAN MAKANAN/ MINUMAN BERBASIS MOBILE WEB (Information Technology and Telematics, 2014)
Abstract-- In connection with increasingly advanced technology and developing, creation of a system that is made in accordance with the specifications and requirements that exist both in the everyday and the world of work. Food and beverage ordering system is needed in order to provide convenience and comfort for the customer and the restaurant. The author designed a system of ordering food and beverages with the intent and purpose of making better quality of service and efficient. The system is built using the PHP programming language and MySQL database. The results of this system, the ordering process that occurs will be easier because the waiter just brought the gadget for orders. Then after ordering automation consumer orders will be sent to the cashiers and cooks, so it will be more efficient ordering process.Keywords: Booking System food drinks, ordering menu.